Megaproject governance's impact on mega construction project CPEC success: the mediating role of agile project management and the moderating effects of project complexity and project management office. - Syed Arslan, Haider (2024)
In the last few decades, mega project governance has become an essential subject for discussion in project management literature. Organizations used the project governance approach to meet the organizational objectives and goals. Yet, many projects fail, and the reasons are sometimes obscure because of the many problems involved in the governance and management of a project. Therefore, current study examined the influence of mega project governance on mega construction project success through mediating role agile project management, moderating effects of mega project complexity and the project management office as a moderated moderator. Data were collected from 327 project managers, middle management personnel, and CEOs involved in various mega construction projects in Pakistan under CPEC, utilizing purposive and convenience sampling techniques. The Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach was employed to test the hypotheses using SmartPLS 4 software. The results indicate that mega project governance significantly and positively influences the success of mega construction projects. Furthermore, agile project management was found to mediate this relationship, demonstrating a positive and significant effect. Additionally, mega project complexity was observed to have a negative and significant moderating effect on both mega project governance and project success, while not significantly impacting the relationship between mega project governance and agile project management. Lastly, the project management office was found to be a significant moderated moderator, reducing the effects of both mega project complexity on mega project governance and the success of mega construction projects, as well as between mega project governance and agile project management. These findings demonstrate that mega project governance within a company, supported by effective agile project management, is the primary driver of sustained high performance and successful completion of mega construction projects. These results will make a valuable contribution to the field of project management.